The Role of the Talent Management Strategy in Achieving the Entrepreneurial Performance of the Organization - Abdulzahra Ali, Asrar (Journal of Advanced Research in HR and Organizational Management, 2023)
The research aims to identify Determination talent management dimensions of (attracting talent, developing talent, directing talent, performance management talent, retain talent) in the entrepreneurial performance of the organization dimensions of (advance planning, efficiency, effectiveness), so search occupies the extreme importance of being treated important and recent issue of the performance Entrepreneuria, management talent, aware of the importance of the subject and expected results of the company surveyed, was an analysis of data obtained through field visits in addition to the questionnaire and interviews, highlights were the results that have been reached to take the sample into account all the management requirements knack of attracting talent and developing talent and directing talent and performance management talent and retain keep talent oriented strategic her towards outstanding performance in their work in accordance with the environmental requirements, that the surveyed banks assess their employees according to achieve in performance leading banks The most important recommendations increase senior management attention attracting talent management performing talent and develop talent and to prepare human cadres imaginatively, through better attract talent and then increase training programs and courses outside the organization to clarify the concept of talent management and its importance in the Entrepreneurial to the goals of the organization, access to global developments in this area. How to cite this article: Ali AA. The Role of the Talent Management Strategy in Achieving the Entrepreneurial Performance of the Organization. J Adv Res HR Organ Mgmt 2022; 9(3&4): 26-44.